Effect of Aerosolization and Drying on the Viability of Pseudomonas syringae Cells - Alsved, Malin; Holm, Stine; Christiansen, Sigurd; Smidt, Mads; Rosati, Bernadette; Ling, Meilee; Boesen, Thomas; Finster, Kai; Bilde, Merete; Löndahl, Jakob; Šantl-Temkiv, Tina (Frontiers in Microbiology, 2018)
Airborne dispersal of microorganisms influences their biogeography, gene flow, atmospheric processes, human health and transmission of pathogens that affect humans, plants and animals. The extent of their impact depends essentially on cell-survival rates during the process of aerosolization. A central factor for cell-survival is water availability prior to and upon aerosolization. Also, the ability of cells to successfully cope with stress induced by drying determines their chances of survival. In this study, we used the ice-nucleation active, plant pathogenic Pseudomonas syringae strain R10.79 as a model organism to investigate the effect of drying on cell survival. Two forms of drying were simulated: drying of cells in small droplets aerosolized from a wet environment by bubble bursting and drying of cells in large droplets deposited on a surface. For drying of cells both in aerosol and surface droplets, the relative humidity (RH) was varied in the range between 10 and 90%. The fraction of surviving cells was determined by live/dead staining followed by flow cytometry. We also evaluated the effect of salt concentration in the water droplets on the survival of drying cells by varying the ionic strength between 0 and 700 mM using NaCl and sea salt. For both aerosol and surface drying, cell survival increased with decreasing RH (p < 0.01), and for surface drying, survival was correlated with increasing salt concentration (p < 0.001). Imaging cells with TEM showed shrunk cytoplasm and cell wall damage for a large fraction of aerosolized cells. Ultimately, we observed a 10-fold higher fraction of surviving cells when dried as aerosol compared to when dried on a surface. We conclude that the conditions, under which cells dry, significantly affect their survival and thus their success to spread through the atmosphere and colonize new environments as well as their ability to affect atmospheric processes.